Porphyridum Cruentum as a natural colorant in chewing gum - Toker, Omer Said (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2019)
In this study, usage possibility of the dried Porphyridium cruentum type microalga biomass in the chewing gum formulation as a natural colorant was investigated. For this aim, the effect of different spray dryer inlet temperatures (150-200 degrees C) on pigment (total carotenoid and chlorophyll-a) quantities and color properties (L-star, a(star), b(star) and C-star) of Porphyridium cruentum type microalga biomass were examined. P. cruentum were cultured using the tubular photobioreactor and harvested by centrifugation. The dried microalga was then added to chewing gum at different concentrations (0.5% and 1.0% w: w) as a natural red colorant. The amount of the total carotenoids in dried biomass ranged from 112.6 to 419.9 mu g g(-1) and chlorophyll-a from 511 to 1513 mu g g(-1). Considering sensorial analysis, algal taste increased with increasing microalga concentration (p < 0.05). The studied factors had no significant effect on cohesiveness, (0.186-0.254), springiness (0.713-0.806) and resilience (0.014-0.015) parameters in chewing gums (p < 0.05). However, a(star) value in chewing gum samples increased with drying temperature and usage amount (from 10.5 to 18.7) which increased red color intensity. According to the findings of the present study, it can be concluded that P. cruentum biomass had a potential use in chewing gum matrix.
Keywords: microalgae; coloring agent; natural; spray dryer; confectionery; CHLORELLA-VULGARIS; BIOMASS; STABILITY; Food Science & Technology